Exploring Resilience and Spirituality among Recovery Drug Addicts in Drug Rehabilitation Center - Mohamad Yasin, Nurhafizah; Shafie, Amin Al Haadi; Baharudin, Dini Farhana (Universitas Negeri Padang, 2024)
Research has shown that lack in resilience may contribute to relapse among former drug addicts. Furthermore, spirituality is recognized as a factor that can positively influence resilience levels. This study investigates the connection between resilience and spirituality among individuals undergoing treatment in drug rehabilitation centres. The objectives were to assess: (1) the level of spirituality among drug addicts, (2) the level of resilience among drug addicts, and (3) the correlation between spirituality and resilience. Using a correlational research design and quantitative methodology, data were collected from 224 participants who are inmate from drug rehabilitation centre. The Connor-Davidson Resilience Scale (CD-RISC) and the Ummatic Personality Inventory (UPI) were utilized to measure resilience and spirituality, respectively. Results indicated that most participants demonstrated moderate levels of spirituality (75%) and resilience (62.5%). A significant positive relationship between the two variables was found (Pearson’s r = 0.665, p < 0.001), indicating that higher levels of spirituality are associated with increased resilience among drug addicts in rehabilitation.